Capturing The Meaning of Life and Self-Love Among Transgender Women: Unveiling Experiences, Family Impacts, and Struggles in Achieving a Meaningful Life - Graciella Florence Kusila; Arthur Huwae (Bulletin of Counseling and Psychotherapy, 2023)
Transwomen is an abbreviation for transgender women, individuals who choose a gender that differs from their biological sex. Previous studies have identified discrimination and issues related to the gender identity and sexuality of trans women. This research aims to portray the meaning of life for trans women in Palangkaraya. Participants were selected through snowball sampling. Data were collected through observations and interviews. This research employs a descriptive phenomenological data analysis to delve into the life experiences of trans women in detail and depth. This research study revealed a new theme, which encompasses the aspect of self-love as a part of the lives of trans women participants in their pursuit of a meaningful life. In this study, it was observed that trans women in the city of Palangkaraya undergo various and challenging life processes in their quest for a meaningful existence. Factors such as family, relatives, employment, thought patterns, attitudes, and personality play a crucial role in guiding trans women towards living a meaningful life and achieving true meaningfulness in life.